KOLIYESTIYKIST ASPHALT CONCRETE BASED BITUMEN VARIOUS GRADES - , В. К., О. О. (Municipal economy of cities. Series: «Economy science», 2013)
The results of experimental studies of the stability of asphalt from road bitumen various grades to the accumulation of residual strains in a rut.